أثر جهدين هوائي ولا هوائي في بعض متغيرات الدم وسرعة الاستشفاء لدى لاعبي ( 100م ) ( 3000 م) - أحمد، نبهان حميد; عبدالرحمن، إيثار حمدي; عبدالرحمن، عمر حمدي (جامعة بابل - كلية التربية الرياضية, 2016)
The research aims to identify The impact of aerobic and anaerobic efforts on some blood changes and the speed of healing amongspeed runners. The researchers used the descriptive approach due to its suitability to the research nature. The research sample consisted of 10 runners, who were chosen randomly by lot for the purpose of applying the exploratory experiment. Two runners were excluded. 4 runners in the aerobic efforts and 4 runners in the anaerobic efforts. The pulse rate, rest time were measured. The blood sample was taken and then a warm up session was done for 10 minutes. Later on, the test was conducted and after that the assisting working team measured pulse rate for the tested sample. The researchers recommended that the coaches had to continuous testing to the blood changes for a different period of time, and to pay attention to it because it affects the chemicalism of power production in muscles.
هدف البحث إلى التعرف على اثر الجهدين الهوائي و اللاهوائي على بعض متغيرات الدم وسرعة الاستشفاء لراكضي السرعة والمطاولة واستخدم الباحثون المنهج الوصفي لملاءمته طبيعة بحثه وقد كان عدد أفراد العينة (10 عدائين ) وتم اختيار عدائين بالطريقة العشوائية عن طريق القرعة لغرض تطبيق التجربة الاستطلاعية وتم استبعادهم من عينة البحث . (4عدائين للجهد الهوائي ـ 4عدائين للجهد اللاهوائي) إذ تم قياس النبض وقت الراحة وتم سحب عينة الدم ومن ثم القيام بإجراء الإحماء لمدة (10) دقائق وبعد ذلك تم إجراء الاختبار وبعد الانتهاء من إجراء الاختبار قام فريق العمل المساعد بقياس النبض للمختبرين وتم بعدها سحب عين الدم وثم قياس النبض في نهاية كل دقيقة وحتى الدقيقة العاشرة . واوصى الباحثون يجب على المدربين إجراء الفحوصات التتبعية لمتغيرات الدم وبصورة مستمرة ولفترات زمنية مختلفة والاهتمام بها ، لأنها تؤثر على كيميائية انتاج الطاقة في العضلات .
Keywords: التدريب الرياضي -- ألعاب القوى -- المهارات الرياضية -- التدريب الرياضي